2020
DOI: 10.1002/ijfe.1965
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic operating efficiency and its determining factors of listed real‐estate companies in China: A hierarchical slack‐based DEA‐OLS approach

Abstract: This study uses a dynamic slacks‐based measure (SBM) model in a data envelopment analysis (DEA) framework with surplus reserve and accounts receivable as desirable and undesirable indicators respectively, based on inter‐connectivity between consecutive periods to estimate the operating efficiency of 110 listed Chinese real‐estate companies in the first step analysis. The results show that 35 listed real‐estate companies in China operated on the efficient frontier by maintaining sustainable growth throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
(49 reference statements)
0
7
0
1
Order By: Relevance
“…The potentials of sustainable development, as well as competitiveness of corporations that results in a higher-quality development, has been described in most of the studies of the same interest [55]. There are various parameters through which one can measure higher-quality development and, among them, apart from other parameters, are rate of profit, return on assets (ROA), Tobin Q, earning per share, return on total assets, and asset turnover rates, which can all be used to calculate the efficiency of corporations and their performance [56,57]. The primary purpose behind establishing a firm, and a traditional managerial policy of the majority firms, has been to multiply profits while the balanced-approach organizations will comply stakeholder's preferences in a real-world situation.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%
“…The potentials of sustainable development, as well as competitiveness of corporations that results in a higher-quality development, has been described in most of the studies of the same interest [55]. There are various parameters through which one can measure higher-quality development and, among them, apart from other parameters, are rate of profit, return on assets (ROA), Tobin Q, earning per share, return on total assets, and asset turnover rates, which can all be used to calculate the efficiency of corporations and their performance [56,57]. The primary purpose behind establishing a firm, and a traditional managerial policy of the majority firms, has been to multiply profits while the balanced-approach organizations will comply stakeholder's preferences in a real-world situation.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%
“…The choice of indicators is a prominent aspect of measuring the efficiency of DMUs (Lu et al, 2019; Mantri, 2008). Following extant literature (Atta Mills et al, 2020), this paper models operating efficiency as depending on the following indicators: fixed assets, capital, operating costs, and employee number as input indicators; revenue, gross profit, and return on equity (ROE) as output indicators; and surplus reserve as a desirable carryover indicator. Please refer to Figure 3 for the dynamic operating process used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…McDonald (2009) suggested that efficiency estimates are fractional data rather than censored data as evidence for the applicability of least squares instead of Tobit regression in determining efficiency drivers. The authors follow McDonald's (2009) and Atta Mills et al's (2020) method to using the least‐squares method and present the model as θo,tgoodbreak=αgoodbreak+β1X1italicotgoodbreak+goodbreak+βnXnotgoodbreak+ϵot, where θo,t denotes the dynamic operating efficiency of company o in period t, β represents the regression coefficient, X indicates drivers of operating efficiency (independent variables), and ϵ is the random error term.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skor efisiensi teknis digunakan sebagai variabel dependen karena terdiri dari efisiensi teknis murni dan skala efisiensinya. 20 Hal ini mengungkapkan bahwa semua hal dianggap sama, peningkatan atau penurunan leverage oleh perusahaan real estate menyebabkan perubahan efisiensi yang tidak signifikan pada periode penelitian. Namun hasil penelitian ini berbeda dengan peenelitian yang dilakukan oleh Chen dan Li tahun 2017.…”
Section: Gambar 6 Peringkat 10 Besar Emiten Properti Dan Real Estate Yang Menjadi Rujukanunclassified